8.5 µm‐Thick Flexible‐Rigid Hybrid Solid–Electrolyte/Lithium Integration for Air‐Stable and Interface‐Compatible All‐Solid‐State Lithium Metal Batteries. Issue 24 (11th April 2022) - Zhang, Kun; Wu, Feng; Wang, Xinran; Weng, Suting; Yang, Xiaoyu; Zhao, Huichun; Guo, Ruiqi; Sun, Yuheng; Zhao, Wenbin; Song, Tinglu; Wang, Xuefeng; Bai, Ying; et al.
Abstract: All‐solid‐state lithium batteries (ASSLBs), as the next‐generation energy storage system, potentially bridge the gap between high energy density and operational safety. However, the application of ASSLBs is technically handicapped by the extremely weak interfacial contact and dendrite growth that is prone to unstabilize solid electrolyte interphase (SEI) with limited electrochemical performance. In this contribution, air‐stable and interface‐compatible solid electrolyte/lithium integration is proposed by in situ copolymerization of poly(ethylene glycol methacrylate)‐Li1.5 Al0.5 Ge1.5 (PO4 )3 ‐lithium (PEGMA‐LAGP‐Li). The first‐of‐this‐kind hierarchy provides a promising synergy of flexibility‐rigidity (Young's modulus 3 GPa), high ionic conductivity (2.37 × 10 −4 S cm −1 ), high lithium‐ion transfer number ( t Li+ = 0.87), and LiF‐rich SEI, all contributing to homogenized lithium‐ion flux, significantly prolonged cycle stability (> 3500 h) and obvious dendrite suppression for high‐performance ASSLBs. Furthermore, the integration protects lithium from air corrosion, providing insights into a novel interface‐enhancement paradigm and realizing the first ASSLBs assembly in ambient conditions without any loss of specific capacity. Abstract : An air‐stable and interface‐compatible hierarchy is proposed by in‐situ co‐polymerized PEGMA‐LAGP‐Li integration. The first‐of‐this‐kind integration provides promising synergy of flexibility‐rigidity (Young's modulus 3 GPa), high ionic conductivity (2.37 × 10 −4 S cm −1 ), high lithium ion transfer number ( t Li+ = 0.87) and LiF‐rich solid electrode interphase, all contributing to homogenized lithium ion flux, prolonged cycle stability (>3500 h) and dendrite suppression for high‐performance all‐solid‐state lithium metal batteries.